An Evaluation of the ISPC Science Fora - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2014)
The ISPC recently conducted a self-evaluation of the Science Forum series as a core mechanism for mobilizing science in terms of identifying new science needs and opportunities, and forging new partnerships. The purpose of this evaluation was to gauge the extent to which the SFs met their objectives, document their merits and shortcomings and detail the major lessons learned.